EL RETABLO BARROCO EN ASTURIAS - Germán Ramallo Asensio (Imafronte, 1989)
Despite of destructions and disappearances, Asturias offers a very important baroque retable-making activity, as in other purrs of Spain. This activity was mainly carried out in convents, monasteries, great parish churches and the cathedral of Oviedo itself, which was enriched with beatiful baroque retables during the XVIIth and XVIIIth centuries. In this richness, several types may be found -rosary-retahles, exedra-retables-; the- all show an interesting iconography, like that in the main altar of the Jesuits' ancient church, in Oviedo. During the first half of the XVIIth century, the Asturian reredos still shows the Manierism as may be observed in the main altar in the monastery of Cornellana and others, though the Baroque spirit stars to be perceived in certain cases like the retables in St. Vincent's Benedictine monastery, today in the Oviedo Council, and at the altar of the collegial church in Cangas del Narcea. Baroque schemes are successful during the second half of the XVIIth century, with works like the retables in ihe Cámara Santa [Holy Chamher] in Oviedo, in the monastery ff San Pelayo, in the same city. and in the monatery of Belmonit. During the XVIIIth century they are built so important retables as the ones in the Jesuits' ancient church in Oviedo and in the Christe King's chapel in the cathedral of Oviedo. The highest baroque and the progression to rococo are represented. among other examples, by the lnmaculate Conception's reredos at the cathedral, and the retable in the Dominicans' church. both at Oviedo.